Using electrophysiology to demonstrate that cuing affects long-term memory storage over the short term - Maxcey, Ashleigh M. (Psychon Bull Rev, 2015)
As researchers who study working memory, we often assume that participants keep a representation of an object in working memory when we present a cue that indicates that object will be tested in a couple of seconds. This intuitively accounts for how well people can remember a cued object relative to their memory for that same object presented without a cue. However, it is possible that this superior memory does not purely reflect storage of the cued object in working memory. We tested the hypothesis that cued presented during a stream of objects, followed by a short retention interval and immediate memory test, change how information is handled by long-term memory. We tested this hypothesis using a family of frontal event-related potentials (ERPs) believed to reflect long-term memory storage. We found that these frontal indices of long-term memory were sensitive to the task relevance of objects signaled by auditory cues, even when objects repeat frequently such that proactive interference was high. Our findings indicate the problematic nature of assuming process purity in the study of working memory, and demonstrate how frequent stimulus repetitions fail to isolate the role of working memory mechanisms.